ВИЗУАЛЬНЫЙ ОБРАЗ КОСТЮМА: ФИЛОСОФИЯ МОДЫ В ВИЗУАЛЬНЫХ ИССЛЕДОВАНИЯХ - ЦАРЕВСКАЯ, Е. Ю. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Проблема исследования феномена моды и индустрии моды заключается в том, что основная база исследовательских материалов предыдущих лет (это прежде всего социологические и семиотические) не раскрывают в полной мере сущности этого феномена. Поэтому актуальным на данный момент является смещение акцента в визуальное поле, и таким образом, междисциплинарное и более широкое. Т.к. индустрией моды образец создается виртуально, не как вещь, а как образ, имеет место типологизации визуального модного образа. Царевська О.Ю. ВІЗУАЛЬНИЙ ОБРАЗ КОСТЮМУ: ФІЛОСОФІЯ МОДИ У ВІЗУАЛЬНИХ ДОСЛІДЖЕННЯХ Проблема дослідження феномена моди та індустрії моди полягає в тому, що основна база дослідницьких матеріалів попередніх років (це насамперед соціологічні та семіотичні) не розкривають повною мірою сутності цього феномена. Тому актуальним на даний момент є зміщення акценту в візуальне поле, і таким чином, міждисциплінарне і більш широке. Т.я. індустрією моди зразок створюється віртуально, не як річ, а як образ, має місце типологізації візуального модного образу. Ключові слова: індустрія моди, модний образ, візуальність, фатіческій модний образ, образ-інсталяція, подіумний образ. Tsarevska E.U. VISUAL IMAGE OF COSTUME: PHILOSOPHY OF FASHION IN THE VISUAL STUDIES Each of the classical concepts reflected the social nature of fashion as it was in a certain era. The modern fashion is a specific phenomenon, that appears as industry. Fashion like industry is specialized production of modern and original models which is organized on the principles of rationality. Understanding of what is produced not an actual model, but trendy - modernity and originality becomes essential. They express, respectively, the desire for otherness, identity, on the one hand, and general following for all "spirit of the time" on the other. The fashion industry has created a virtual model, not as a thing, but as an image. This situation is similar to what J. Bodriiar describes, saying about the priority models of reality. [2] In today’s fashion world the spread of samples across reference groups are simulated. The models in the magazines and TV ads are served not only as an object of a certain size, color, texture, but as a desired image of social status, interpersonal relationships, etc. Photographers and designers are not so much concerned with showing all the features of the model, but rather the creation around it the virtual social environment. By engaging in the process of changing fashion models, people not only acquire and use things but bring the model into social reality. Fashion, as it becomes the industry, is the reproduction of social reality in the form of its simulation. Thus, by far the most extensive observations on the mechanism of fashion are accumulated regarding to his external appearance and his costume. This fact LV Petrov explains in following: architecture, music, painting professionally are involved in small groups. The clothes are worn by all. That is why in the appearance of man the fashion is most clearly and visibly, and is universal [13, p.4]. During this period, fashion has been studied mainly as a mass communication process, because in the operation mode involves in its sphere large groups of people and fashion messages occur with the use of technical means of information reproduction (press, radio, television, film). B.D.Parygin sees fashion as a specific and dynamic form of standardized mass behavior that occurs mostly spontaneously under the influence of the dominant attitudes in society and rapidly changing tastes and hobbies. The author considers the etymology of the fashion and comes to the conclusion that the etymological definition of fashion does not reveal its social essence, but it shows that the concept of fashion is socio-historical. Although the word "fashion" has penetrated into all the European languages, but it has failed to dislodge them from the other words related to it within the meaning of "taste", "fancy", "style", "hobby", and others. Therefore Parygin considers necessary to consider the relationship of concepts of fashion and taste, custom, culture, and advertising. The results of this review are: taste as a type of fashion let people in ancient times to give subjects of aesthetic appreciation of his work. Fashion - on the one hand, is the stage in the development of mass taste, and on the other hand – is a form of development. Fashion - is a form of public taste that exists objectively regardless of our individual consciousness, taste. The structure of society influences on fashion and taste, stratifying them. In the mass consciousness of the everyday phenomenon of fashion it’s often related only to the specific cultural sphere - a sphere of clothing. Obviously, such an approach is due to vagueness of the concept of fashion, which, on the one hand, the meaning of some of the phenomena that are characterized by high variability in any culture, and on the other hand - the same phenomenon only in culture clothing. Such inconsistency of meaning often leads to differences in understanding the phenomenon of fashion. But the same problem we face, for example, using the concept of "culture." On the one hand a culture understands all that man can do, all aspects of his activities, and the other - in this concept are invested purely ethical or aesthetic sense. Key words: Fashion industry, visual Studies, fashionable image, phatic fashionable image, image-installation, podium image, semiotics.